Research on Join Operation of Temporal Big Data in Distributed Environment - ZHANG Wei,WANG Zhijie (Ji suan ji gong cheng, 2019)
Distributed system is an ideal choice for processing temporal large data join operation,but the existing distributed system cannot support the original temporal join query and cannot meet the processing requirements of temporal large data with low latency and high throughput.Therefore,a two-level index memory solution scheme based on Spark is proposed.The global index is used to prune the distributed partitions,and the local temporal index is used to query the partitions in order to improve the efficiency of data retrieval.A partition method is designed for temporal data to optimize global pruning.Experimental results based on real and synthetic datasets show that the scheme can significantly improve the processing efficiency of temporal join operation.